The design and synthesis of cell-penetrant autophagy-inducing peptides and the development of a novel assay for measuring cell penetration - Peraro, Leila. (2018)
Abstract: Biotherapeutics are gaining popularity as efficient modulators of protein-protein interactions. However, accessing intracellular targets remains a significant hurdle for developing them into drugs. Cell-penetrating peptides (CPP) have been studied extensively for their penetration properties and have been used as carriers for small and large biotherapeutics. Though they have been employed in numerous clinical applications, their immunogenicity and poor systemic distribution, has prevented them from advancing in the drug development pipeline. Strategies have been emerging to render bioactive peptides intrinsically cell-penetrant. One of the most successful approaches has been peptide stapling, which locks a peptide into a specific conformation and can yield high binding affinity, resistance to proteolytic degradation, and improved biological activity. But it is still not well understood what biochemical and structural modifications specifically affect cell penetration. This dissertation describes the use of a diversity-oriented stapling approach to generate intrinsically cell-penetrant, autophagy-inducing peptides. In addition, to investigate the cell penetration of these peptides, a novel quantitative assay was developed which can report on penetration with subcellular resolution. Chapter 1 describes the design and synthesis of autophagy-inducing peptides derived from the autophagy regulator Beclin 1. Diversity-oriented bis-alkylation was applied to optimize intrinsically cell-penetrant autophagy inducers. The most potent stapled peptide, DD5-o, was shown to be active in vivo and in a cellular model of Huntington's disease. Chapter 2 highlights further structure-activity relationship studies conducted on DD5-o, as well as structural determination. The solution structure of DD5-o in methanol revealed α-helical conformation stabilized by an unusual (i,i+3) staple, cross-linking two D-cysteines. iv In producing the autophagy inducer DD5-o, the diversity-oriented bis-alkylation strategy was shown to be a promising avenue for rendering peptides more cellpenetrant. The mechanism and limitations of this reaction were studied, and methods for monitoring progression of the reaction were developed. These details are described in Chapter 3. Chapter 4 provides an overview of current methods used for measuring cell penetration, as well as the design and setup of the chloroalkane penetration assay (CAPA). This assay was benchmarked to known CPPs and the data demonstrated that CAPA can accurately report on cytosolic penetration in a quantitative manner. Chapter 5 shows different applications of CAPA. Due to its flexibility and high throughput, it was used for cell penetration profiling of different peptides. Temperature, serum content, and time are factors that can affect the extent of cell penetration, and we showed that the effects of each can be quantified using CAPA. CAPA was also applied to investigate the structure-penetration relationships of bioactive peptides. It was further applied to measure the uptake of nanoparticles, as well as to measure nuclear penetration using a different cell line. Our data to date show that CAPA is an exciting tool for measuring and profiling the cell penetration of biotherapeutics.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Chemistry.; Advisor: Joshua Kritzer.; Committee: Charles Mace, David Walt, and Loren Walensky.; Keyword: Chemistry.